Coffee Commodity Supply Chain Design Using Business Model Canvas and Analytical Hierarchy Process Case Study Of Coffee IKM/UKM In West Java - Toto Ramadhan, MT; Yogi Yogaswara; Dela Rachmania Nurhasanah; Lisanie Nur Fitrianie Permana (Jurnal Info Sains : Informatika dan Sains, 2023)
Coffee is one of Indonesia's natural riches. West Java has quite a potential coffee commodity. Where West Java has an area of 43,555 ha with a total production of 20,732 tons per year. Based on this, there is a need for research to develop coffee in West Java This research approach method is firstly using the Business Model Canvas which consists of 9 elements or nine building blocks. The second study is the Analytical Hierarchy Process to process data. This method is carried out to determine the influence of the BMC segment on each tire of the coffee supply chain. The third study is to analyze the condition of the coffee supply chain in West Java The calculation results for the supply chain are as follows: At the farmer level the influence is channels with a value of 0.20. , At the SME level the influence is key partnership with a value of 0.46. , At the distributor level the influences are channels and cost structure with a value of 0.24. , At the retail/outlet level, the influence is customer relationship with a value of 0.46. At the consumer level, the influence is key resources with a value of 0.09.